Physicochemical and optical properties of carbon quantum dots synthesized from watermelon peels for photovoltaic application - Zaini, Muhammad Safwan (2024)
The characteristics of carbon quantum dots (CQDs) are significantly influenced by various factors such as preparation method, carbon source, doping and others. Therefore, a comprehensive investigation into the optimal properties of CQDs is crucial for their targeted application. In this study, CQDs were synthesized from watermelon peels using a carbonization method. A thorough examination of their properties was conducted, considering key parameters such as the type of solvents used, carbon concentration, and pH values with consideration for their application in dye-sensitized solar cells (DSSC). The solvatochromic effect was observed, manifesting as variations in the photoluminescence (PL) spectra when CQDs were prepared in different solvents. PL measurements conducted at different excitation wavelengths, revealed that the emissions of CQDs were distinctly influenced by the polarity of the solvents. Dynamic light scattering (DLS) analysis confirmed that the size of CQDs ranged approximately from 5.80± 0.4 to 9.74± 0.5 nm, a correlation validated by high-resolution transmission electron microscope (HRTEM) results. In the study on carbon concentration, the findings demonstrate a pronounced impact on the stability of CQDs particles. Zeta potential findings indicated that the stability of CQD particles peaked at low carbon concentration, with zeta potential values of -62.4 mV and -64.3 mV for CQDs dispersed in ultrapure water and methanol, respectively. Additionally, fluorescence intensity increased parallel with carbon concentrations, and the study identified that CQDs synthesized at 0.05-0.07 g/ml concentrations exhibited superior stability in colloidal form. In exploring different pH conditions, consistent pH-independent PL peak emissions were observed, yet the intensities displayed a pH-dependent trend, amplifying from acidic to neutral and diminishing from neutral to alkaline conditions. Moreover, in addressing drying concerns, the study revealed the occurrence of the coffeering effect at pH 2.5, while uniform deposition was achieved at pH 7.5. This phenomenon was discussed based on Derjaguin, Landau, Verwey, Overbeek (DVLO) theory. For the application of CQDs in DSSCs, CQDs in methanol demonstrated the highest efficiency of 1.23%, surpassing CQDs in ultrapure water (0.038%) and the control sample N719 dye (0.34%).